Central action of α-adrenoceptor agents on the baroreceptor reflex - Ockert, Detlef M.; Czachurski, Jürgen; Dembowsky, Klaus; Seller, Horst (Journal of the autonomic nervous system, 1992)
In chloralose-anaesthetized cats the effects of intravenous application of the α1- and α2-adrenoceptor agonistic and antagonistic agents methoxamine, prazosin, B-HT 933 and rauwolscine were tested on baroreceptor reflex, sympathetic background activity and blood pressure. Sympathetic activity was recorded from the renal nerve and the efficacy of the central transmission of the baroreceptor reflex was measured by the duration of the complete inhibition of renal nerve activity during electrical stimulation of the left carotid sinus nerve. All baroreceptors were denervated by sectioning both carotid sinus and vagal nerves. The α1-agonist methoxamine increased baroreceptor-induced sympathoinhibition, sympathetic background activity and blood pressure. The α1-antagonist prazosin had the opposite effects. The α2-agonist B-HT 933 was most effective in augmenting the inhibitory response in sympathetic activity to baroreceptor stimulation; sympathetic background activity and blood pressure were also decreased. At low doses (50 μg/kg) the α2-antagonist rauwolscine reduced the baroreceptor sympathetic reflex inhibition and increased sympathetic activity and blood pressure. The effect of B-HT 933 upon the baroreceptor reflex could be completely antagonized by rauwolscine. These findings demonstrate a very effective facilitation of the baroreceptor reflex transmission by stimulation of central α2-adrenoceptors. Through such humoral-neuronal interaction circulating catecholamines are likely to modulate cardiovascular control.
Elektronische Reproduktion der Druck-Ausgabe 14. März 2003
Gesehen am 21.10.2024